ALTERNATIVE THERAPIES TO BACTERIAL INFECTIONS OF THE ORAL CAVITY: A REVIEW - Amodu, Samuel; Ojelabi, Ayotundun Christianah; Udochukwu, Tochukwu Favour (FUDMA Journal of Sciences, 2026)
Oral infections are among the most prevalent global health conditions and are intrinsically linked to dysbiosis of the oral microbiome and biofilm ecology. In health, a balanced microbial community supports mucosal integrity and immune homeostasis. However, shifts driven by dietary sugars, poor oral hygiene, smoking, systemic disease, and antibiotic exposure promote pathogenic polymicrobial biofilms implicated in dental caries, periodontitis, peri-implantitis, and endodontic infections. These biofilm-mediated diseases, commonly involving Streptococcus mutans, Porphyromonas gingivalis, Fusobacterium nucleatum, and Aggregatibacter actinomycetemcomitans, are not only locally destructive but are increasingly associated with systemic conditions including cardiovascular disease, diabetes, rheumatoid arthritis, Alzheimer’s disease, and infective endocarditis. Antimicrobial resistance (AMR) further complicates management, with global mortality exceeding one million deaths annually and a substantial proportion of dental antibiotic prescriptions deemed unnecessary. Conventional therapies such as mechanical debridement combined with antiseptics and systemic antibiotics, provide short-term microbial reduction but are limited by incomplete biofilm penetration, disruption of commensal microbiota, adverse effects, and accelerating resistance. Emerging strategies such as bacteriophage therapy, nanoparticle-based antimicrobials, photodynamic and photothermal therapies, and antimicrobial peptides offer targeted, biofilm-disruptive, and resistance-sparing alternatives. These approaches demonstrate promising antimicrobial efficacy while aiming to preserve microbial balance. However, challenges, including toxicity concerns, regulatory barriers, cost, and limited long-term clinical evidence, remain. Advancing precision antimicrobial interventions may redefine oral infection management by shifting from broad elimination to ecological modulation and targeted biofilm control.